New media, new advertisers a critical discourse analysis on Filipino beauty Tiktok content - Marcelo, Kriscia Anne Sabino
This study uses the Political Economy as a framework to understand why beauty TikTok content can persuade its viewers to buy beauty products and promote consumerism among its audiences. Using Fairclough's Three-Dimensional Critical Discourse Analysis as a theory and method, I subjected 20 existing Beauty TikTok Content of Filipino TikTok creators with product mention to textual analysis. I interviewed three beauty TikTok influencers and facilitated a focus group discussion of beauty TikTok viewers for processing analysis. Through social analysis, I investigated the context of beauty TikTok content's production, consumption, and distribution. This study contributes to the limited research on TikTok and understands the platform through the lens of the Political Economy. I uncovered the language and strategies prevalent in the Filipino beauty TikTok community to help viewers realize the impetus of their purchasing decisions and create informed consumers who know when they are being exposed to advertisements.